Effectiveness of Ureteric Reimplantation on Non-Refluxing Obstructive Congenital Megaureter (Bangladesh Journal of Urology, 2020)
Background: One in ten thousand children born with megaureter. A significant portion of this groups are of obstructed variety and the rest are refluxing ureter. It can cause obstructions and back pressure renal damage. Early diagnosis and treatment can stop deterioration of renal function and prevent complications like renal failure. Definitive treatment is uretero-neocystostomy with or without tailoring the ureter.Objective: Objective of this study was to observe the effectiveness of ureteric reimplantation on non-refluxing obstructive congenital megaureter. To achieve this objective we had observed serum creatinine level pre and postoperatively and assessed structural changes in kidney by ultrasonogram, IVU, MCU and RGP pre and postoperatively. We also observed the split renal function and split GFR of the affected kidney both pre and post operatively.Methods: This was a cross-sectional observational study. This study comprise of 35 cases of congenital non-refluxing obstructed megaureter, who were admitted in BIRDEM General Hospital and multiple other hospitals in Dhaka city from July 2013 to December 2014. Diagnosis was made by intravenous urography (IVU) reveling a dilated lower third or entire ureter with narrow tapering lower end. Obstruction was also confirmed by diuretic Tc99m DTPA scan. A voiding cystourethrogram was obtained to exclude VUR. Those with poor renal function were evaluated by ultrasonography, DTPA scan and retrograde ureteropyelography.Results: Of 35 patients, 20 were male and 15 were female. Age range 2 to 19 years. All patients underwent ureteric reimplantation, with tailoring in 15 cases. Post-operative mean serum creatinine was 0.99±0.34 which showed improvement. Split function in DTPA renogram and split GFR of patient with POM in the affected right side also showed improvement (29.49±4.02 and 29.64±4.86) as well as affected in left side (27.77±4.18 and 28.02±5.31).Conclusion: Ureteral tailoring with an extravesical ureteral reimplantation can be performed safely and effectively for primary obstructive megaureter. It is found that, ureteroneocystostomy ensured free renal drainage and preserved renal function as well as prevented complications and further deterioration.Bangladesh Journal of Urology, Vol. 21, No. 1, January 2018 p 20-24